2021
DOI: 10.1186/s40834-021-00159-4
|View full text |Cite
|
Sign up to set email alerts
|

Improving public health service delivery response to address contraceptive needs of socio-economically disadvantaged HIV positive people in Maharashtra, India

Abstract: Background People living with HIV (PLHIV) receive free antiretroviral treatment (ART) in public health facilities of India. With improved life expectancy, unmet sexual and reproductive health needs of PLHIV have to be addressed through a converged programmatic response strategy. Evidence shows that socioeconomically disadvantaged women are most vulnerable to high reproductive morbidities, especially HIV positive women with an unmet need of contraception. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Medley et al similarly found dual contraceptive use was 9% pre-intervention compared to 18% post-intervention ( 29 ). Joshi et al reported 0% dual contraception uptake pre-intervention compared to 44.6% at the endpoint ( 33 ). Mantell et al observed a 10% absolute increase in use of dual contraceptives in the intervention group compared to the control ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medley et al similarly found dual contraceptive use was 9% pre-intervention compared to 18% post-intervention ( 29 ). Joshi et al reported 0% dual contraception uptake pre-intervention compared to 44.6% at the endpoint ( 33 ). Mantell et al observed a 10% absolute increase in use of dual contraceptives in the intervention group compared to the control ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…All studies examined the effect of integration on contraceptive uptake with the most frequently used categories being dual method and modern contraceptive use (Table 2). Out of the six studies investigating dual method contraceptive use, five suggested an association between integration and increased dual method use (29)(30)(31)(32)(33). Chen et al, a cross-sectional study, found 30% of individuals attending non-integrated facilities use dual methods compared to 40% at integrated services (p < 0.01) (30).…”
Section: Associations Between Fp-hiv Integration and Contraceptive Up...mentioning
confidence: 99%